Impact of tapioca adhesive on water-holding capacity in pot compost for tomato nurseries - Lohita, Erika Ajeng Nawang; Andriyani, Idah; Novita, Elida; Nadzirah, Rufiani; Jourdain, Damien (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Water supply is one of the determining factors for successful production during tomato cultivation. Many farmers still carry out vegetable seedling activities using polybags and provide water daily. This research aims to find out whether this potting compost can store water well to be an alternative to polybags as a planting medium. Pot compost with tapioca adhesive has good water absorption and storage capabilities, which can help increase water storage capacity, reducing the need for irrigation water. This research uses a descriptive analysis method with the parameters measured including vegetative growth, length and width of cracks in compost pot, and compost weight before and after watering. The vegetative observations of tomato plants showed that treatment T1 had better growth than treatments T2 and T3 in plant height which averaged 56.40 mm and an average number of leaves of 5.20 strands on day 14. However, treatment T2 had better shape resistance than treatment T1 which only had an average crack length of 25 mm and an average crack width of 2.20 mm. In observations of measuring the water holding capacity of pot compost, treatment T3 was found to be the most optimal in storing water because on day 6 it still stored 12 ml of water compared to treatments T2 and T1. If this research is applied to large-scale plant nurseries, it can reduce plastic waste originating from polybags.